Gambaran Kadar HbCO dalam Darah pada Masyarakat Dusun Gemeling, Gedangan, Sidoarjo - Devita Rahmah Pratiwi; Hadi Suryono; Demes Nurmayanti (Poltekkes Kemenkes Surabaya, 2018)
Carbon monoxide (CO) is one of the toxic pollutants which is resulted from the emission of mobile sources and immovable sources. The inhaled CO will go into the lungs then into the bloodstrea. For instance, it will compete with oxygen to bind the hemoglobin. CO-hemoglobin bond forms hemoglobin carboxy (HbCO) which is 200-300 times stronger than the oxygen bond with Hb. As consequence, oxygen is pushed out from its bond with Hb. This study aims to determine the description of blood HbCO levels in the community of Demeling Hamlet due to CO exposure from roads located in Gedangan and cooking oil factory nearby.This research is descriptive research with cross sectional approach. Samples of HbCO in blood were taken from 12 housewives aas respondets who domiciled in Dusun Demeling and samples of CO in the air (5 points). Technique of sampling in this study used technique of Purposive Sampling. Data collected is analyzed using tabulation descriptively in the form of tables.The results showed that HbCO levels in the blood of respondents living nearby Gedangan had an average of 9.98% and respondents living close to the cooking oil factory with an average of 8.68%. Average of ambient CO levels in the air around Gedangan was 11456.04 μg / Nm3 and area near the cooking oil factory was 2063.07 μg / Nm3. Respondents aged 40 years had an average HbCO in blood of 11.54% and the age of ≤40 years had an average of 6.24%.Respondents living 5 years had an average HbCO of 9.34%. Respondents whose location near Gedangan roads had average HbCO levels higher than respondents near the cooking oil factory because motor vehicle activity lasts for 24 hours. At last, to reduce CO content in the ambient air, it is hoped that people can create green environment by planting plants around their house. Keywords : HbCO content, Carbon monoxide, Road